Issues of Peace and Security in Contemporary Nigeria - OLUWASANMI, Busuyi Víctor; OLUWASANMI, Ayodele C.; OJO, Sunday Kayode (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2022)
The issue of insecurity in contemporary Nigeria has become a threat to both internal and international peace and security with ever growing violence and attacks on security forces, civilians, churches, media houses as well as international bodies such as the United Nations. Consequently, we examine the complex issues that have affected the peace and security of contemporary Nigeria. This is done with the aim of finding solutions that can lead to success in fending off insurgency in contemporary Nigeria. Data used for this study was sourced from peace and security bulletin, books, newspapers and related journal articles on security issues. Using ordinary historical analysis, the result shows that the apparatus of peace and security earlier employed by the Nigerian state is inadequate. The findings of this paper identified the individuals as the centrepiece from where the household, community, the local government area, the state and the federation evolve and revolve as peace and security circles of different radii. It posited that peace and security concerns are in circles and actors within each circle are better attuned to concentrate and manage the peace and security challenge therein. This paper thus suggests the need for decentralization of the police and other state owned agencies of internal security management in order to mitigate the upsurge in crime and violence including those emanating from armed robbers, political assassins, ransom kidnappers, oil thieves, and Islamic insurgents among others.